Differential ability of the dorsal and ventral rat hippocampus to exhibit group I metabotropic glutamate receptor–dependent synaptic and intrinsic plasticity. (24th January 2017) - Tidball, Patrick; Burn, Hannah V.; Teh, Kai Lun; Volianskis, Arturas; Collingridge, Graham L.; Fitzjohn, Stephen M.
Background: The hippocampus is critically involved in learning and memory processes. Although once considered a relatively homogenous structure, it is now clear that the hippocampus can be divided along its longitudinal axis into functionally distinct domains, responsible for the encoding of different types of memory or behaviour. Although differences in extrinsic connectivity are likely to contribute to this functional differentiation, emerging evidence now suggests that cellular and molecular differences at the level of local hippocampal circuits may also play a role. Methods: In this study, we have used extracellular field potential recordings to compare basal input/output function and group I metabotropic glutamate receptor-dependent forms of synaptic and intrinsic plasticity in area CA1 of slices taken from the dorsal and ventral sectors of the adult rat hippocampus. Results: Using two extracellular electrodes to simultaneously record field EPSPs and population spikes, we show that dorsal and ventral hippocampal slices differ in their basal levels of excitatory synaptic transmission, paired-pulse facilitation, and EPSP-to-Spike coupling. Furthermore, we show that slices taken from the ventral hippocampus have a greater ability than their dorsal counterparts to exhibit long-term depression of synaptic transmission and EPSP-to-Spike potentiation induced by transient application of the group I mGluR agonist ( RS )-3, 5-dihydroxyphenylglycine. Conclusions: Together, our results provide further evidence that the information processing properties of local hippocampal circuits differ in the dorsal and ventral hippocampal sectors, and that these differences may in turn contribute to the functional differentiation that exists along the hippocampal longitudinal axis.